2009
DOI: 10.1111/j.1476-5381.2009.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone via upregulation of Akt/eNOS pathways attenuates dysfunction of endothelial progenitor cells, induced by advanced glycation end products

Abstract: Background and purpose: Advanced glycation end products (AGEs) and endothelial progenitor cells (EPCs) play key roles in pathogenesis of diabetes-related vascular complications. AGEs can induce dysfunction in EPCs. The peroxisome proliferatoractivated receptor-gamma (PPARg) agonists are widely used in the treatment of type 2 diabetes, and it remains unknown if they could attenuate EPC dysfunction induced by AGEs. Experimental approach: EPCs isolated from healthy adults were cultured with various concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 52 publications
5
72
0
1
Order By: Relevance
“…Furthermore, rosiglitazone increased EPC survival, differentiation, and function, which were impaired by C-reactive protein (CRP) (26). Another study reported that rosiglitazone ameliorated AGE-induced dysfunction of EPCs via activation of the PI3K-Akt-eNOS signal pathway (27). However, the current findings of mechanisms of rosiglitazone on EPCs mainly included activation of the PI3-kinase/Akt pathway and endothelial nitric oxide synthase, as well as inhibition of the NAD(P)H oxidase activity of progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rosiglitazone increased EPC survival, differentiation, and function, which were impaired by C-reactive protein (CRP) (26). Another study reported that rosiglitazone ameliorated AGE-induced dysfunction of EPCs via activation of the PI3K-Akt-eNOS signal pathway (27). However, the current findings of mechanisms of rosiglitazone on EPCs mainly included activation of the PI3-kinase/Akt pathway and endothelial nitric oxide synthase, as well as inhibition of the NAD(P)H oxidase activity of progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Besides glucose control, RSG shows diverse therapeutic effects in the regulation of endothelial function, cellular apoptosis, tissue fibrosis, and the control of blood pressure. [28][29][30][31][32] In addition, it limits cardiac hypertrophy in diet-induced hypercholesterolemic rats by the renin-angiotensin system. 16) Furthermore, current evidence suggests that it has beneficial effects on CMCs under oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the peroxisome proliferator-activated receptors y (PPARgamma) agonist rosiglitazone increased EPC function via upregulating the AkteNOS signal pathways (58). Pioglitazone increased EPC adhesion to arteries from diabetic patients via an upregulation CIRCULATING ANGIOGENIC CELL DYSFUNCTIONof CXCR4, the receptor for SDF-1.…”
Section: Antidiabetics and Organic Nitratesmentioning
confidence: 99%